Oil, Agriculture, and the Public Sector : Linking Intersector Dynamics in Ecuador - Fiess, Norbert M.; Verner, Dorte (World Bank, Washington, DC, 2014)
In a recent paper, Fiess and Verner (2000) analyse sectoral growth in Ecuador and find significant long-run and short-run relationships between the agricultural, industrial and service sectors. They take this as evidence against the dual economy model which rules out a long-run relationship between agricultural and industrial output and show further that a more detailed picture of the growth process can be discovered, once the agricultural, industrial and service sectors are disaggregated further into intrasector components. This paper extends their initial results and provides insight from a multivariate cointegration analysis of intrasector components. The authors are able to identify three cointegrating relationships, each of which has its own meaningful economic interpretation: Two cointegration relationships capture the direct and indirect effects of the "petrolization" of the Ecuadorian economy. A third relationship clearly indicates a link between agriculture and industrial activity. Since this third cointegrating relationship seems to coincide in time with the trade liberalisation at the end of the 1980s, promoting agriculture appears to be an important way to promote sustainable economic growth in Ecuador.